Distribution patterns of aquatic birds in a high-Andean wetland in southeastern Peru: An approach based on environmental factors - Carlos Lazo; Renny Daniel Diaz; Alexis Díaz; Victor Bustinza; Wilfredo Chavez; Aracely Dayana Machaca; Yoana Yarasca; Edwin Calderon; Maria Masias (PLoS ONE, 2026)
High-Andean wetlands play a crucial role in avian biodiversity conservation, serving as ecological oases in arid mountain regions. These ecosystems face increasing anthropogenic pressures, yet research remains limited, hindering conservation efforts. We investigated aquatic bird distribution patterns in Lake Piuray (southeastern Peruvian Andes) and their relationship with environmental variables like water depth and chlorophyll-a content. From December 2022 to November 2023, we conducted monthly surveys at 13 points across four lake zones representing natural and altered habitats. Using interpolation and additive models, we analyzed relationships between aquatic bird abundance and environmental factors, comparing seasonal and zonal differences. We recorded 44 aquatic bird species (19,768 individuals). Areas with depths < 1 m and intermediate-to-high chlorophyll-a levels (I543 index: 0.20–0.25) showed highest abundance and richness. Lakeshore beaches supported greater aquatic bird concentrations than deeper zones. At the family level, shorebirds (Charadriidae and Recurvirostridae) preferred shallow waters, while diving birds (Anatidae and Podicipedidae) tolerated greater depths. Although community-level metrics showed no seasonal differences, six families exhibited abundance variations between wet and dry seasons: Phalacrocoracidae, Scolopacidae, and Recurvirostridae were more abundant in wet seasons, while Charadriidae, Laridae, and Phoenicopteridae peaked in dry seasons. These results highlight the importance of shallow areas with high chlorophyll-a concentrations for the conservation of aquatic birds in high-Andean wetlands. This study is one of the few to analyze the influence of environmental and temporal factors on the distribution of high-Andean aquatic birds, and its representative nature makes it a valuable model for identifying priority areas for the conservation of these species.